EFFECT OF FINANCIAL LITERACY, FINANCIAL ATTITUDE, AND FINANCIAL INCLUSION ON FINANCIAL BEHAVIOR - Sjahmagri Priatama Sukma; Mahir Pradana (Jurnal Riset Bisnis dan Manajemen, 2022)
Students who are financially dependent on parents and financial-independent students are affected by Covid-19. Preventing financial problems can be carried out by good financial literacy. Based on precedent studies, financial literacy in Telkom University students was good; however, in reality, a protest emerged regarding tuition fees, generating a gap between the theory and reality. This study aimed to test a financial literacy argument of Telkom University students and the reality during pandemic. The study employed a quantitative method, verificative description, and purposive non-probability sampling technique. The study respondents amounted to 100 students of Business Administration undergraduate study. Data were analyzed using path analysis. From the hypothesis testing results, the financial literacy variable affected financial attitude, financial inclusion, and financial behavior. The inclusion variable affected and mediated the effect of financial literacy on financial behavior. Meanwhile, financial attitude did not affect and mediate the effect of financial literacy on financial behavior. Keywords: Financial; Financial Literacy, Financial Attitude; Financial Inclusion; Financial Behavior; Students